1973
DOI: 10.1084/jem.137.6.1419
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Dependent Generation of Chemotactic Activity in Serum

Abstract: The recognition that different host defense mechanisms against injury are closely interrelated has permitted a clearer understanding of the processes of inflammation, blood coagulation, and activation of serum proteolytic enzyme systems. Human blood platelets are cells primarily specialized for hemostasis. However, they have also been found to possess inflammatory functions characteristic of polymorphonuclear leukocytes and may therefore play a broader role in host defenses (1).Leukocytes promote inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

1974
1974
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(30 citation statements)
references
References 19 publications
(15 reference statements)
2
27
0
1
Order By: Relevance
“…Weksler and Coupal (24) have demonstrated that a factor present in an acid-soluble extract of human platelets can release chemotactically active C5a from C5. At the present time it is not certain whether the property of human platelets that initiates formation of the C5-9 complex is related to the C5-splitting activity described by these investigators.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Weksler and Coupal (24) have demonstrated that a factor present in an acid-soluble extract of human platelets can release chemotactically active C5a from C5. At the present time it is not certain whether the property of human platelets that initiates formation of the C5-9 complex is related to the C5-splitting activity described by these investigators.…”
Section: Resultsmentioning
confidence: 99%
“…This reaction proceeds in the presence of EDTA and epsilonamino-N-caproic acid (EACA), suggesting that it is not initiated by the classical or alternative pathways of complement activation and also differs from C5-cleaving platelet factor of Weksler and Coupal (24). METHODS Preparation of platelet-rich plasma, washed platelets, washed erythrocytes, platelet-free plasma, and serum.…”
Section: Introductionmentioning
confidence: 99%
“…Since the platelet and granulocyte evolved from a common cell, the amebocyte (41), it was not surprising to find collagenase activity in the platelet granules. Indeed, an increasing number of proteins thought to be characteristic of leukocytes has been demonstrated in platelets, including mediators of vascular permeability (42), bacteriocidal process (43), elastic tissue destruction (3), and chemotaxis (44). This study indicates that collagenase, perhaps derived from the granules of platelets, may be available under certain conditions to play a role in the inflammatory process.…”
mentioning
confidence: 87%
“…Platelets have been shown to influence a wide variety of physiological processes of not only hemostasis but also inflammation through the actions of released products [1][2][3][4][5][6]. It has been reported that platelet release products (PRPr) involve several substances that enhance human leukocytic phagocytosis [7,8].…”
Section: Introductionmentioning
confidence: 99%